A Brief Account of Homoeopathic Approach to Fight COVID-19 Disaster - Rath, Padmalaya; Jana, Shib Narayan (Homœopathic Links, 2020)
Disasters are unfortunate but integral part of civilisation. While the incidence of disaster cannot be prevented altogether, the effects can be modified to the extent that there will be minimum or no loss of life, minimum loss to property and quick restoration to normalcy. Virtually in many instances effects can be reduced to nil or negligible if sufficient diligence is practiced. Epidemic diseases are regarded as disasters too. Homoeopathy is a medical system of therapeutics which claims to have effective intervention in epidemics. Any system of medicine that offers to intervene in any epidemic should be embraced. Epidemics have occurred in the past not only in India but in other countries as well, such as Cholera, Asian flu, Spanish flu, severe acute respiratory syndrome and Avian influenza. When an epidemic spreads in wider geographical area and affects large number of people, it is termed as pandemic. Coronavirus disease 2019 (COVID-19) is a pandemic that began in December 2019.Homoeopathic system of medicine claims to have effective treatment in epidemics. But hardly any effort seems to have been made to correlate the limited documented studies on epidemics that may consolidate the positive results of homoeopathy in such a way that can help policy makers to give a serious thought to the fact that homoeopathy can be trusted to combat epidemic diseases. This article involves data collection using existing published articles on case series/individual cases in peer-reviewed journals assessing the applicability of homoeopathy in epidemics/pandemics and in COVID-19. With such a background finding suitable solutions is a necessary step toward prevention and treatment of epidemic diseases.
Keywords: COVID-19; disaster; epidemic; homoeopathy; pandemic